2020
DOI: 10.1128/aem.01265-20
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxybutyrate Derived from Poly-3-Hydroxybutyrate Mobilization Alleviates Protein Aggregation in Heat-Stressed Herbaspirillum seropedicae SmR1

Abstract: Under conditions of carbon starvation, thermal-, osmotic- or oxidative-shocks, mutants affected in the synthesis or mobilisation of PHB are known to survive less well. It is still unclear if the synthesis and accumulation of PHB are sufficient to protect bacteria against stress conditions, or if the stored PHB has to be mobilised. Here, we demonstrated that mobilisation of PHB in Herbaspirillum seropedicae SmR1 was heat shock activated at 45°C. The in situ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Similarly, the ∆phaC mutant of R. eutropha is reported to be more sensitive to low temperature than the wild type (Nowroth et al 2016). Alves et al (2020) demonstrated that PHB mobilization is the key to survival of H.…”
Section: Phb Accumulation and Mobilization Is Important For Bacteria ...mentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, the ∆phaC mutant of R. eutropha is reported to be more sensitive to low temperature than the wild type (Nowroth et al 2016). Alves et al (2020) demonstrated that PHB mobilization is the key to survival of H.…”
Section: Phb Accumulation and Mobilization Is Important For Bacteria ...mentioning
confidence: 95%
“…Furthermore, mobilization of PHB in H. seropedicae SmR1 was activated by a heat shock at 45°C, and mutants that lacked the capacity to synthesize or mobilize PHB were more susceptible to heat shock (Alves et al 2020). Recent results showed that Pseudomonas extremaustralis, a highly stress-resistant strain, exhibits a high UV radiation resistance in conditions favoring PHB accumulation.…”
Section: Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC 6803 [ 22 , 27 ]. Secondly, the environmental stresses could induce PHB production in microorganisms by supporting bacterial viability under adverse environments, such as heat stress, oxidative stress, high salinity [ 2 , 3 , 7 , 28 ]. Third strategy relates to genetic and/or metabolic engineering approach.…”
Section: Introductionmentioning
confidence: 99%
“…From a biological point of view, the main purpose of PHA in bacterial cells is the storage of carbon and energy. Furthermore, it has been recently reported that the presence of PHA granules, as well as a complex PHA metabolism, can also enhance the robustness and resistance of bacterial cells to numerous stress factors, such as fluctuations in osmotic pressure [ 14 ], heating [ 15 ], freezing-thawing [ 16 ], UV irradiation [ 17 ], or oxidative pressure [ 18 ]. Actually, several very recent reviews are dedicated to the stress-protective function of PHA for prokaryotic cells [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%